Soviet Household Saving: A Cross-Section Study of Soviet Emigrant Families - Ofer, Gur; Pickersgill, Joyce (Quarterly Journal of Economics, 1980)
This study examines the saving patterns of Soviet households by developing a saving function based on cross-section data derived from a family budget survey of Soviet emigrants. The results are very similar to those of Western studies. While saving is a positive function of current income, the average rate of saving rises only relatively mildly with income, indicating that current income from the public sector is much more “permanent” than in market economies. The proportion of income earned from the private sector that is saved is much higher—indicating that it is highly transitory and risky. The long-run saving rate is, by international comparison, rather low.